PERAN EMAS SEBAGAI SAFE HAVEN BAGI SAHAM PERTAMBANGAN DI INDONESIA PADA PERIODE PANDEMI COVID-19 - Yuliana, Ashalia Fitri; Robiyanto, Robiyanto (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2021)
The purpose of this study is to analyze the role of gold as safe haven or hedge for mining stocks in Indonesia during the COVID-19 pandemic period. The data used in this study are mining stock index data (JASICA) daily closing on the Indonesia Stock Exchange and daily closing gold price data on the international market during the period January 2020 - May 2020. Data analysis was performed using QREG to see the potential of gold as a safe haven and GARCH 1.1 to see the potential of gold as a hedge. The results of this study are gold can serve as a robust safe haven for Indonesian mining stocks when there is extreme shocks occur in the stock market. In addition, in this study gold also can serve as a hedge for mining stocks in Indonesia. So investors are advised when the Indonesian Capital Market conditions are experiencing uncertainty as it is today and investors want to move their assets into safe and liquid instruments, gold is the first choice for investors to secure their assets because gold is proven to be the safe haven.